Experiences of Online UniversityExaminations: A Case of Nepal (Comparative & International Education Series, 2022)
Higher authorities’ traditional thinking, negligence, and negative attitude are the key obstacles to Nepal’s online education and examination system. This paper aims to report on the university examiners’ and examinees’ experiences with online examinations after the outbreak of the COVID-19 crisis in Nepal. It analyzes how they managed online examinations with their limited skills, applications, and resources of ICT. Based on qualitative research, it employed semi-structured interviews to collect primary data from purposively selected university teachers, students, and administrative staff. This paper reports that university teachers and administrative staff worked hard to conduct the online examinations, and students managed to face them. Nepal’s findings suggest that the formation of appropriate policy and its practical implementation to establish suitable web-based systems, servers, applications, advanced ICT infrastructure, and capacity development of human resources could ease the quality management of online examinations in higher education. How to cite in APA Acharya, B. N., Khadka, T. B., Lamichhane, R. P., & Sharma, R. K. (2022). Experiences of online university examinations: A case of Nepal. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 105-118). STAR Scholars.